Common genetic variants on chromosome 9p21 confers risk of ischemic stroke: A large-scale genetic association study - Li, Rongyao; Zhang, Xinyue; Yin, Wei; Wang, Yuzhuo; Liu, Ying (Cellular and Molecular Biology, 2021)
The objective of this experiment was to observe the allele frequency and genotype distribution of some 9p21 SNPs in the Anhui Han population, and to study its relationship with the susceptibility to ischemic stroke. For this purpose, a collection of 992 patients with ischemic stroke confirmed and hospitalized in our hospital from October 2017 to October 2020 were used as the IS case group, and 951 normal people who had a healthy physical examination in the physical examination center of our hospital during the same period were selected as the control group. After informed consent, cubital venous blood of all subjects was collected, and epidemiological data of the subjects were collected; the rs2383206, rs2383207, rs10757274, and rs1333049 on chromosome 9p21 as the sites to be tested, using Sequenom Mass Array system for genotyping, using Haploview4.2 software to calculate whether the genotype distribution meets Hardy-Weinberg equilibrium. Results showed that there were no significant differences between the two groups in gender, age, and smoking history. There are significant differences in the levels of hypertension, diabetes and hyperlipidemia, total cholesterol, triglycerides, HDL-C and apolipoprotein A1 between the two groups of study subjects. The genotype frequencies of the participating populations were in a balanced state. The results of the association analysis between SNPs and IS susceptibility showed that rs2383207, rs10757274, rs1333049 and rs2383206 are the susceptibility sites of ischemic stroke. It concluded that in Anhui, China, the inheritance of chromosome 9p21 region is associated with ischemic stroke.